EVALUASI DAYA SIMPAN DAGING DARI SAPI BALI YANG DIGEMBALAKAN DI AREA TPA DESA PEDUNGAN, DENPASAR SELATAN - Samudra I W. G. A.; I N. T. Ariana; S. A. Lindawati (Jurnal Peternakan Tropika, 2016)
The purposes of this research were to determine the microbial profile and storability of beef which cattle grazing at landfill area (T1). The object of this research was bali cattle that looked after at TPA Pedungan Village, South Denpasar. This research was carried out for 2 months, in Wayan Sija’s traditional abatoar located at Banjar Bersih, Darmasaba Village and microbiology test in Product Technology and Microbiology, Faculty of Animal Science, Udayana University. This research used a Completely Randomized Design (CRD) by two treatments with six repitations. The results of the research showed that microbial profile TPC unsignificant difference (P>0.05), Coliform and E.coli bacteria showed a significant difference (P<0.05) between T1 and T0. Observations storability at 0 hour showed unsignificant results (P>0.05), but observations next 2 hours, 4 hours, 6 hours, 8 hours and 10 hours showed a significant difference (P<0.05) , Conclusions of this research showed that the microbial profile TPC between Ti and T0 is higher but still at the threshold of food safety, while Coliform and E.coli between T0 and T1 is same contamine of patoghen microbial. Storability of T1 is only 10 hours while T0 is12 hours.